Knowledge, attitude and practice among dentists of Gujarat regarding medico-legal issues - Bhatia, Gunjan A.; Shah, Anvi R.; Sharma, Devdatt J.; Nakhuda, Fatema M.; Mehta, Dhwani G.; Sodani, Vasudha (International Journal Of Community Medicine And Public Health, 2023)
Background: Law concerns with every field of human life and dentistry is no exception. Therefore, knowledge of legal aspects is as important as knowledge of medicine in life of health care professionals. The patient-dentist relationship had undergone a significant transition over the past few decades with upsurge anxiety in the community and increased lawsuits against dentists. Thus, a health care professional must know about medico-legal problems to protect oneself from legal issues. Methods: A cross-sectional questionnaire was pre-tested among the group of 10 professionals prior to the study. It was made available to dental practitioners residing in Ahmedabad city. It was mandatory to answer all the questions. Data was collected through online survey forms and were subjected to descriptive statistics. Results: The results showed that there was lack of knowledge in majority of dentists regarding medico-legal issues. Nearly half (53%) of the participants were unaware concerning consumer protection act and 81.33% of the candidates were not aware regarding minimum duration for the preservation of dental records. Around 56% were unaware about revised code of ethics and less than half know about negligence and non-negligence acts. Conclusions: The present study depicted that majority of the dentists lack knowledge concerning medico-legal issues. Therefore, seminars should be arranged to intensify their knowledge regarding legal facets or more information should be added in dental curriculum.